Itineraries of Margaret of Valois (with Reference to her Letters from the National Library of Russia) - Shishkin, Vladimir V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article examines the itineraries of Margaret of Valois (1553–1615), Queen of Navarre, during her stay in the south of France between the late 1570s and early 1580s, which coincided with the crucial phase of the Religious Wars between Catholics and Huguenots. The main source for the study of these itineraries are the letters of Queen Margaret from the National Library of Russia, which make part of the collection of Peter Dubrovsky. The article traces the history of letters of the Queen of Navarre in St Petersburg, and it is suggested that the carton of the documents (Autograph 57) is part of the personal archive of State Secretary Villeroy. The author also analyses new data on the princess’ itineraries during her childhood, based on the new electronic database, as well as the historiography of the question of her movement, which makes it possible to understand the place of the St Petersburg autographs in the reconstruction of Margaret’s unknown itineraries in 1579–1582. Most of Margaret’s letters were written in territories ruled by Henry of Navarre, in Guyenne and Gascony and Navarre and represent an array of 32 documents of great importance, which help determine exactly where the Queen went to, indicate the trajectory of her movement, specify the duration of her stays in particular localities, and respectively, suggest possible delivery times for letters to recipients, mainly to her brother Henry III and her mother, Catherine de’ Medici. The study of Margaret’s messages from the point of view of her itineraries also helps place them in the historical context of religious and political events of the Civil Wars period in France, identify the details of the peacemaking role of the Queen in the south of the country, as well as understand the mechanisms for the implementation of peace treaties and decisions by the opposing parties.